Evaluating Corporate Governance Reforms In Indonesia: Compliance, Challenges, And Pathways Forward Under Company Law - Putera, Fauzan Ravinda; Lewiandy, Lewiandy (Riwayat: Educational Journal of History and Humanities, 2025)
This research paper evaluates corporate governance reforms in Indonesia, focusing on the operationalization and effectiveness of Good Corporate Governance (GCG) principles under Company Law No. 40 of 2007 and Capital Market Law No. 8 of 1995, along with implementing regulations like OJK's POJK No. 21/POJK.04/2015. Addressing two key research questions, the study examines how legal provisions translate GCG ideals into practices for publicly listed companies and assesses the framework's consistency, adequacy, and enforceability in promoting transparency, accountability, and minority shareholder protection. Employing a qualitative methodology through document analysis and thematic synthesis of legal texts, OJK reports, and case studies, the findings reveal that while mandates for board structures, disclosures, and shareholder meetings effectively operationalize GCG in theory, practical implementation is hindered by enforcement weaknesses, cultural factors in family-owned firms, and jurisdictional overlaps. Real cases, such as the Jiwasraya scandal, illustrate governance failures despite clear legal requirements. The analysis concludes that the framework is adequate but requires harmonized enforcement and reforms to enhance compliance and investor confidence. Pathways forward include strengthening OJK oversight and integrating digital tools for better effectiveness.